Evaluation of Wi-Fi Mesh Networks for Reading Electricity Consumption - Bazán Prieto, Carlos (2024)
In Smart electrical networks, the Advanced Metering Infrastructure allows bidirectional communication between the service company and the customers. It includes smart meters and a communication infrastructure, which among other functions, is responsible for reading electricity consumption and billing. Cable or wireless technologies are used for the exchange of information between the networks that comprise it. In Cuba there is no such Advanced Metering Infrastructure, the reading of electricity consumption is carried out manually by an operator, reader-collector. That is why we are working on a project where traditional meters are modified by adding a Wi-Fi communications module that allows wireless access. This work evaluates the possibility of interconnecting several modified meters with wireless modules to form a mesh network. Protocols, programming tools, metrics to evaluate performance, scenarios, and experiments are described. As a result, the possibility of forming a mesh network is verified, with the exchange of information, with the requirements of self-configuration and self-repair of the network. This allows the reader-collector to read consumption from any point on the network through a smart device.